The role that cultural differences play on individual perception of brand image - Mavuso, Sibonelo (The IIE, 2020)
Brand communicators need to become aware of difference within cultures and consumer behaviour to stay competitive in today‟s business environment. Even though brands aim to communicate the same image, the image of those brands may still be perceived differently due to differences in cultural values. The aim of this study is to explore how cultural differences among consumers affect the perception of brand image, mainly among young adults in Johannesburg. Previous literature provided evidence that people in different cultures do not process information in the same way (Baldwin, Coleman, Gonzalaz & Shenoy-Packer, 2014). Since brand meaning is to a great extent the result of human interpretation it is thus predicted that brand meanings differ across cultures. The problem being studied is that many times, a brand will need to adapt their offerings to different cultures because the culture is the prime determinant of consumers' attitude and behaviours (Jandt, 2015). To fulfil the purpose of this research a qualitative research approach was applied. Seven semi-structured interviews were conducted with participants studying at a higher institution in Johannesburg. To facilitate the data analysis, the main steps of thematic analysis were used. By use of Hofstede‟s Cultural Dimensions Theory the analysis yielded that brand image can have different meanings for individuals, and that culture can influence the way individuals perceive a brand. This study seeks to provide brand communicator's with deep insight into consumers' cultural behaviour, as scholars have previously stated the same brand image cannot hold universal meaning. This is imperative because a clear brand image conveys the success of the product and gives results with increased sales and revenues.
Keywords: Brand image; Perception; Cultural differences